Infection Characteristics of Clonorchis sinensis Metacercariae in Fish from Republic of Korea - Sohn, Woon-Mok (Korean journal of parasitology, 2022)
The infection nature of Clonorchis sinensis metacercariae (CsMc) in freshwater fish hosts is closely related to the transmission of human clonorchiasis. This article reviewed the infection characteristics of CsMc in freshwater fish in the Republic of Korea (Korea). The status of CsMc infection was examined in a total of 17,792 cyprinid fish of 49 species in 9 water systems, which included Hantan-/Imjin-gang, Han-gang, Geum-gang, Mangyeong-gang, Yeongsan-gang, Tamjin-gang, Seomjin-gang, Nakdong-gang, and streams in the east coastal areas from 2010 to 2020. The infection status of CsMc was examined according to cyprinid fish species and water systems, after which analyzed by endemicity and susceptibility index. The high endemicity was shown in the cyprinid fish from 3 regions (6.1%) in the upper reaches of Nakdong-gang, such as Banbyeon-cheon (stream), Yongjeon-cheon, and Wi-cheon. The moderate levels were observed in fishes from 8 regions (16.3%), and low endemicity was shown in fishes from 20 regions (40.8%). No CsMc were detected in fish from 18 regions (36.7%). The susceptibility of CsMc in index fish, Puntungia herzi, was found to be a reliable index without examination of other fish species. CsMc infection rates were closely related to subfamily groups in the cyprinid fish hosts in a highly endemic area. In Korea, a total of 58 fish species in 10 families has been listed as the second intermediate hosts for C. sinensis. This review provides several novel features of CsMc infection and clarifies the species of second intermediate freshwater fish host in Korea.